Targeting Oxidative Stress and Inflammation to Prevent Ischemia-Reperfusion Injury - Wu, Liquan; Xiong, Xiaoxing; Wu, Xiaomin; Ye, Yingze; Jian, Zhihong; Zhi, Zeng; Gu, Lijuan (Frontiers in Molecular Neuroscience, 2020)
Cerebral ischemia injury can result in neuronal death and/or functional impairment, leading to further damage and dysfunction after the recovery of blood supply. Cerebral ischemia/reperfusion injury (CIRI) often causes irreversible brain damage and neuronal injury and death, which involves many complex pathological processes including oxidative stress, amino acid toxicity, the release of endogenous substances, inflammation, and apoptosis. Oxidative stress and inflammation are interactive and play critical roles in ischemia/reperfusion injury in the brain. Oxidative stress is important in the pathological process of ischemic stroke, and is critical for the cascade development of ischemic injury. Oxidative stress is caused by ROS during cerebral ischemia and is more likely to lead to cell death, and ultimately brain death, after reperfusion. During reperfusion especially, superoxide anion free radicals, hydroxyl free radicals, and nitric oxide (NO) are produced, which can cause lipid peroxidation, inflammation, and cell apoptosis. Inflammation alters the balance between pro-inflammatory and anti-inflammatory factors in cerebral ischemic injury. Inflammatory factors can therefore stimulate or exacerbate inflammation and aggravate ischemic injury. Neuroprotective therapies for various stages of the cerebral ischemia cascade response have received widespread attention. At present, neuroprotective drugs mainly include free radical scavengers, anti-inflammatory agents, and anti-apoptotic agents. However, the molecular mechanisms of the interaction between oxidative stress and inflammation, and their interplay with different types of programmed cell death in ischemia/reperfusion injury, are unclear. The development of a suitable method for combination therapy has become a hot topic.